2002
DOI: 10.1002/ar.10062
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of gut‐associated lymphoid tissue in calf and chicken

Abstract: The calf contains two types of Peyer's patches (PPs): jejunal and ileal. The ileal PP has been thought to be equivalent to the bursa of Fabricius (BF) as a central lymphoid organ. The morphologies of ileal and jejunal PPs in the calf were compared with those of the BF and the caecal tonsil (CT) in the chicken. Immunoglobulin G-positive (IgG ϩ ) cells appear in the follicles of them all and exhibited a dendritic appearance after birth. We investigated whether the IgG in these follicles was produced in situ. IgG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
28
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 45 publications
4
28
0
3
Order By: Relevance
“…The role of the Peyer's patches [38,57,58] and the mesenteric lymph nodes as inductive sites for mucosal immune responses is well established and will not be discussed much further in this review. Similarly, it is of interest that the single continuous ileal Peyer's patch differs in structure from the jejunal Peyer's patches in many domestic species such as sheep [23,41,43], cattle [57,58], pigs [2,3,8], dogs [29] and buffalo [1] and may act as a primary lymphoid organ involved in the generation of a B cell repertoire, as does the chicken bursa of Fabricius [2,42].…”
Section: Organised Lymphoid Tissuementioning
confidence: 99%
“…The role of the Peyer's patches [38,57,58] and the mesenteric lymph nodes as inductive sites for mucosal immune responses is well established and will not be discussed much further in this review. Similarly, it is of interest that the single continuous ileal Peyer's patch differs in structure from the jejunal Peyer's patches in many domestic species such as sheep [23,41,43], cattle [57,58], pigs [2,3,8], dogs [29] and buffalo [1] and may act as a primary lymphoid organ involved in the generation of a B cell repertoire, as does the chicken bursa of Fabricius [2,42].…”
Section: Organised Lymphoid Tissuementioning
confidence: 99%
“…These organs consist of large interfollicular T-cell areas and dispersed follicular B-cell areas. In addition, many helper T-cell, IgG + cells and IgA + cells were found in these secondary lymphoid organs [9,12]. In the chicken bursal dorsal wall connected bursal duct, the existence of diffusely infiltrated lymphoid tissue called T-dependent area is previously described [2,6].…”
mentioning
confidence: 94%
“…Histologically, densely packed lymphatic follicle and the very few number of T-cell are distributed in the follicle of both primary lymphoid organ [3,9,12]. It has been also reported that secondary lymphoid organ such as calf jejunal PP and chicken caecal tonsil have the functions for local mucosal immunity [1,4,11,12]. These organs consist of large interfollicular T-cell areas and dispersed follicular B-cell areas.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 It is responsible for inducing immune response against bacteria, viral, and parasitic enteric (i.e. introduced via the digestive tract) antigens [2][3][4] as well as responses to innocuous antigens. 5 All this said: how do the bacterial populations that of a "MUST" must attach to the intestinal wall respond to certain feed additives used as suitable/probable alternatives to AGPs?…”
Section: Introductionmentioning
confidence: 99%